2009
DOI: 10.1055/s-0028-1087817
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Synthesis of N-Arylputrescines and Cadaverines

Abstract: We present a two-step, general synthesis of N-arylputrescines and cadaverines, by cesium carbonate mediated alkylation of anilines with w-chloronitriles and subsequent reduction. The cesium-mediated alkylation shows remarkable selectivity towards the monoalkylation product. The method is straightforward and leads to satisfactory global yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The ω - arylaminonitrile precursors were obtained by reaction of the corresponding ω-halonitrile and arylamines, as previously reported by our group [44]. …”
Section: Resultsmentioning
confidence: 99%
“…The ω - arylaminonitrile precursors were obtained by reaction of the corresponding ω-halonitrile and arylamines, as previously reported by our group [44]. …”
Section: Resultsmentioning
confidence: 99%
“…In tetrahydrofuran (THF), acetonitrile, and dimethoxyethane, very low conversion to the desired product was observed. In previous work, we demonstrated that potassium and sodium iodides significantly improve the yields of nucleophilic substitutions, [24] probably because of in situ generation of a more reactive iodoalkyl compound. To test this hypothesis, we next explored potassium and sodium iodides as catalysts.…”
Section: Synthesis Of Phosphonoacetamidesmentioning
confidence: 93%
“…Compounds ( 1 , 5 , 7 , 9 , 10 – 12 , 14 – 15 , 27 , 29 , 33 , 34 , 36 , 37 ), 3 18 , 31 ( 19 , 21 ), 32 22 , 33 ( 23 , 31 , 32 ) 34 were described in the literature.…”
Section: Methodsmentioning
confidence: 99%